Let b = -21 + 27. Solve b = -5*c + 26 for c.
4
Let m be (0 + (-3)/(-5))*5. Solve 0 = -4*f - m - 9 for f.
-3
Let j(t) = t - 3. Let z be j(5). Let l be (-3)/z*(-8)/6. Suppose -l*p - p + 12 = 0. Solve 9 + 7 = -p*b for b.
-4
Let n = 55 + -55. Solve -b + n + 4 = 0 for b.
4
Suppose -2*s + 34 - 8 = 4*w, 3*s - 7 = 2*w. Solve s*i - 1 = 4 for i.
1
Let u = 113 + -112. Solve -5 = 2*h - u for h.
-2
Let t be 17/(-85)*(1 - 1). Solve -4*l = -t*l + 12 for l.
-3
Let p be (-4)/(-12) - (-28)/6. Let g = p - 5. Solve 0 = -b - g*b - 1 for b.
-1
Let g be 2⁄12 + (-262)/(-12). Solve 5*t - g = 3 for t.
5
Let s(t) be the third derivative of t5⁄60 - t4⁄12 + t3⁄6 - 4*t2. Let b be s(2). Let o be (-6)/(-12)*b*4. Solve -1 = -f - o for f.
-1